Biodegradation mechanisms and functional microbiology in conventional septic tanks: a systematic review and meta-analysis. Issue 1 (18th November 2020) - Shaw, Kelsey; Dorea, Caetano C.
Abstract : Knowledge gaps exist pertaining to the interaction between anaerobic conditions, microbiology and activity that characterize biodegradation mechanisms in septic tanks. Abstract : Background : Conventional septic tank (ST) systems are an important and relatively low-cost type of decentralized on-site sanitation infrastructure. Although ST systems are one of the most applied decentralized sanitation technologies globally, limited research has been performed to identify the type and degree of biodegradation mechanisms present within the tanks themselves; which are assumed to occur but have not yet been adequately characterized. Objectives : To assess available literature for evidence supporting the presence and relationship between anaerobic conditions, microbiology and activity by reviewing the current literature on the conventional ST in order to characterize the assumed anaerobic biodegradation mechanisms therein. Methods : A systematic review and meta-analysis was performed in two databases (Web of Science & Google Scholar) along with supplemental literature reporting linkages between STs and the anaerobic characterization of ST sludge. 112 records were found, of which 30 studies were retained that met the review's inclusion criteria. Results : Few studies included data on the conventional ST. Of those that did, data suggests that anaerobic conditions are present. The lack of quality and quantity in the results pertaining to anaerobic microbiology and activity raised concerns regarding the comparability and reliability of these results to accurately characterize biodegradation mechanisms. Conclusions : This review's findings support the assumption that anaerobic conditions are present in a conventional ST; however, due to the lack of robust data regarding anaerobic microbial communities and activity, it cannot be concluded that a ST is treating waste with anaerobic biodegradation processes. These findings highlight the need to further investigate the strength and effects of this relationship, especially in the context of reaching global improved- and sustainable-sanitation targets.